The principle of autonomy as related to personal decision making concerning health and research from an 'Islamic Viewpoint' - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Mohd Shah, Azarisman Shah (2010)
Informed consent is now accepted as a cornerstone of medical practice. It is a derivative of the four fundamental principles of medical ethics, which are patient autonomy, nonmaleficence, beneficence, and justice. Islam upholds the underlying virtue of these four basic principles, but diversity arises in their interpretation and practical applications. In the World Health Report 2000, the World Health Organization opined that the expectation for autonomy was “universal,” while acknowledging cultural differences in its interpretation and implementation. The concept of autonomy applies well in securing the rights of patients against paternalistic infringement and in cases of malpractice. However, in this paper we argue that strict adherence to the Western grounded philosophy of medical ethics and autonomy is insufficient to solve ethical dilemmas in modern medicine, as it denies the role of faith in a supernatural being. Most non-Western cultures are still proud of their communal relations and spiritualistic ethos. In Western bioethics, patient autonomy prevails in choices involving all sectors of social and personal life, a concept unacceptable in many other cultures. In Islamic bioethics, the rights of God, the community, as well as the individual do feature in consideration. Islam emphasizes health promotion and disease prevention, making it obligatory for a Muslim physician to dissuade practices that undermine individual and collective health. Islam encourages individuals to get involved in such research, which has a public benefit and justifies the risks of participation. We propose a more flexible viewpoint that accommodates cultural values in interpreting autonomy and applying it in an increasingly multilingual and multicultural, contemporaneous society.